Political judgement : essays for John Dunn - Bourke, Richard (ed.); Geuss, Raymond (ed.) (New York, 2017)
From Plato to Max Weber, the attempt to understand political judgement took the form of a struggle to define the relationship between politics and morals. This book by leading international scholars in the fields of history, philosophy and politics restores the subject to a place at the very centre of political theory and practice. Whilst it provides a range of perspectives on the theme of practical reason, it also explores a series of related problems in philosophy and political thought, raising fundamental questions about democracy, trust, the nature of statesmanship, and the relations between historical and political judgement. In the process, the volume reconsiders some classic debates in political theory ? about equality, authority, responsibility and ideology ? and offers new and original treatments of key figures in the history of political thought, including Thucydides, Montaigne, Locke, Smith, Burke and Marx.
Keywords: Political science-Philosophy